The influence of authority delegation of property assets managementon time management - Yana Nurahmad Haerudin; Mokhamad Anwar; Supiansyah Supiansyah (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
This research aims to determine the extent to which time management can run effectively at PT Pupuk Indonesia (Persero)., achieved after the management implements the good delegation of authority to manage property assets.  The research method employed was a census of 55 leaders from PT Pupuk Indonesia Group (all related Senior Vice Presidents and Vice Presidents). The data analysis used in this quantitative research approach is descriptive and causal. Meanwhile, it examines both primary and secondary data as well Data were analyzed using PLS-SEM software. The study's results revealed that authority delegation to manage property assets directly impacts improving time management at PT Pupuk Indonesia (Persero). The direct contribution of delegation of authority in improving time management is quite substantial. The qualitative aspect of delegation of authority directly impacts time management, which also tends to be quantitative.